FAKTOR-FAKTOR PENENTU UTAMA KETERLAMBATAN PADA PEKERJAAN KONSTRUKSI PABRIK (STUDI KASUS: PABRIK KAWASAN CIKARANG) - Mardiaman Purba; Indriasari (UKI Press, 2021)
At every stage of a construction project, time is a factor. Delays are common in construction projects. The timing of construction projects is influenced by a number of factors. Furthermore, these factors contribute to the length of time required for implementation. The sequence of factors that cause delays in construction work is examined in depth in this study. The list of delay factors compiled from various sources. Following the screening, the following 6 categories and 57 factors of tardiness were generated in order: 2) ingredients (5); 3) equipment (7); 4) location characteristics (10); 5) managerial (16); and 6) finance (6). These factors were arranged into a structured questionnaire list, which respondents filled out based on their perception trends. A total of 34 people responded to the survey. The Cronbach alpha test was used to test the reliability and validity of the collected data, which was used to determine the factor ranking using average value analysis based on large to small values. The data was processed in the following order based on the categories of the delay's causes: ingredients; labor; managerial; location characteristics; finance; and equipment. Meanwhile, material delivery (B1), a lack of coordination with supervisors (A10), and the need for material counting are the three most important factors (E4). Contractors looking for work in Cikarang and elsewhere should be aware of three major factors that cause delays in industrial construction projects.